Natural history of Mycoplasma genitalium Infection in a Cohort of Female Sex Workers in Kampala, Uganda - Vandepitte, Judith; Vandepitte, Judith; Weiss, Helen A.; Kyakuwa, Nassim; Nakubulwa, Susan; Muller, Etienne; Buvé, Anne; Van der Stuyft, Patrick; Hayes, Richard; Grosskurth, Heiner (Sexually transmitted diseases, 2013)
There have been few studies of the natural history of Mycoplasma genitalium in women. We investigated patterns of clearance and recurrence of untreated M. genitalium infection in a cohort of female sex workers in Uganda. Methods—Women diagnosed as having M. genitalium infection at enrollment were retested for the infection at 3-month intervals. Clearance of infection was defined as testing negative after having a previous positive result: persistence was defined as testing positive after a preceding positive test result, and recurrence as testing positive after a preceding negative test result. Adjusted hazard ratios for M. genitalium clearance were estimated using Cox proportional hazards regression. Results—Among 119 participants infected with M. genitalium at enrollment (prevalence, 14%), 55% had spontaneously cleared the infection within 3 months; 83%, within 6; and 93%, within 12 months. The overall clearance rate was 25.7/100 person-years (pyr; 95% confidence interval, 21.4–31.0). HIV-positive women cleared M. genitalium infection more slowly than did HIVnegative women (20.6/100 pyr vs. 31.3/100 pyr, P = 0.03). The clearance rate was slower among HIV-positive women with CD4 counts less than 350/mL3 than among those with higher CD4 counts (9.88/100 pyr vs. 29.5/100 pyr, P < 0.001). After clearing the infection, M. genitalium infection recurred in 39% women. Conclusions—M. genitalium is likely to persist and recur in the female genital tract. Because of the urogenital tract morbidity caused by the infection and the observed association with HIV acquisition, further research is needed to define screening modalities, especially in populations at high risk for HIV, and to optimize effective and affordable treatment options.
Keywords: Natural history; Mycoplasma genitalium Infection; Female Sex Workers; Uganda